Thermal interface material with graphene enhanced sintered copper for high temperature power electronics. (14th May 2021) - Deng, Shaojia; Zhang, Xin; Xiao, Guowei David; Zhang, Kai; He, Xiaowu; Xin, Shihan; Liu, Xinlu; Zhong, Anhui; Chai, Yang
Abstract: Sintered nano-copper is becoming a promising candidate as thermal interface material (TIM) for die attaching in high power electronics. It exhibits much higher thermal conductivity and operating temperature than conventional TIMs based on polymer and solder joints, and higher electromigration resistance and lower cost than sintered nano-silver TIM. However, the performance of existing sintered nano-copper is lower than expected because of high porosity resulted from poor sintering of copper particles with oxide shell. Here we demonstrate a method of improving the thermal conductivity of sintered copper by addition of graphene/Cu–Cu x O with controllable diameter of ∼163 nm. The measured thermal conductivity of the sintered composite TIM is enhanced by up to 123.5% compared with that of sintered pure copper. It can be understood as a result of the formation of graphene heat transfer network in sintered TIM. In addition, the C–O–Cu bonds formed at the interface between graphene and copper nanoparticles are critical for improving thermal performance as well as electrical and mechanical performance of the TIM. The developed TIM can be widely used in high power electronic packaging especially for high temperature applications, including IGBT, SiC and GaN power devices.